ОРГАНІЗАЦІЯ БАЗИ ДАНИХ ОБ’ЄКТІВ ГЕОЛОГІЧНОЇ СПАДЩИНИ (НА ПІДСТАВІ АНАЛІЗУ ВІДОМОСТЕЙ ПРО ГЕОЛОГІЧНІ ПАМ’ЯТКИ ДОНБАСУ) - Samoilenko, L.V. (Institute of Geological Sciences of the Ukrainian National Academy of Sciences, 2019)
As a result of the analysis of information on geological heritage objects, developed in the process of its research, according to official sources, significant discrepancies, diversity of information on names, sets of features (attributes), and its insufficiency for identification of objects were revealed. The basic principles of the geoinformation system of geological heritage objects of Ukraine are determined and the proposals on classification and creation of the database of geological heritage objects, which are coordinated with the legislative and normative-legal acts of Ukraine, are substantiated. A reasonable set of information (attributes) about geological heritage objects to fill the database.